Cover page - Boothman, Derek (International Gramsci Journal, 2024)
This is the abstract of the cover page of the International Gramsci Journal, issue 19, showing the Liceo Dettori, the high school in Cagliari, attended by Gramsci before he registered for a degree course at the University of Cagliari.